Learning path : full stack JavaScript. - Fhala, Ben; Marcinkevi(breve)cius, Andrew; Heap, Michael; Perrenoud, Michael; Madera, Luke; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2016)
"The increasing popularity of Node.js just goes to show how quickly developers are moving towards using one language across their development stack. In this Learning Path we'll look at MongoDB, Express, AngularJS and Node.js as a comprehensive full-stack JavaScript solution that will help you embrace modern web development"--Resource description page.
Mastering JavaScript / Ben Fhala -- Web development with Node.js and MongoDB / Andrew Marcinkevi(breve)cius -- Mastering express web application development / Michael Heap -- Learning Web development with the MEAN stack / Michael Perrenoud -- Mastering MEAN web development / Luke Madera.
Presenters, Ben Fhala, Andrew Marcinkevi(breve)cius, Michael Heap, Michael Perrenoud, Luke Madera.
Title and publication information from resource description page (Safari, viewed July 11, 2016).
Keywords: Web applications -- Development; JavaScript (Computer program language); MongoDB; Electronic books